F(x) = 2x and G(x) = x^2 + 2
(G - F)(x) just means we subtract the functions from each other.
x^2 + 2 - 2x
Let's rearrange the expression
x^2 - 2x + 2
Answer:
-47.4
Step-by-step explanation:
Answer: $33.00
Step-by-step explanation:
Given
Mr. Claussen needs 15 Pounds of ground beef
It is stated that 2 pounds of beef cost $4.40
Using unitary method
1 Pound cost
For 15 pounds it is
Thus, he has to spend $33 for 15 pound meat
Answer:
c. 138 feet
Step-by-step explanation:
h(t) = −16t^2 + 83t + 33
At3 seconds
h(3) = -16(3^2) + 83(3) + 33
h(3) = -16(9) + 249 + 33
h(3) = -144 + 249 + 33
h(3) = 138
c. 138 feet